2021
DOI: 10.1029/2021gc009965
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Sediment Input at the Nankai Trough Subduction Zone: Implications for Shallow Slow Earthquake Localization

Abstract: Along-strike variations in the structural architecture and accretionary prism taper angle of subduction margins correlate spatially with changes in the seismogenic behavior of the plate interface (Bassett et al., 2014;Fujie et al., 2013;McNeill & Henstock, 2014). Lateral variations in the roughness of the incoming igneous crust and the overlying sediment types and cumulative thickness are thought to modulate the alongstrike variations in accretionary wedge mechanics (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 134 publications
0
9
0
Order By: Relevance
“…Depressions with a NNW‐SSE strike near the trough axis and on the incoming Philippine Sea plate appear in our basement map (features E and F in Figure 3a). These depressions represent grabens, formed during the formation of the Philippine Sea plate (e.g., Kimura et al., 2021), that are filled with thick sediments (e.g., Ike et al., 2008; Tilley et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Depressions with a NNW‐SSE strike near the trough axis and on the incoming Philippine Sea plate appear in our basement map (features E and F in Figure 3a). These depressions represent grabens, formed during the formation of the Philippine Sea plate (e.g., Kimura et al., 2021), that are filled with thick sediments (e.g., Ike et al., 2008; Tilley et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, strong ocean currents offshore Japan (for example, the Kuroshio Current) have been recognized as a dominant agent of routing based on interpretations of clay mineral provenance (Underwood & Fergusson, 1996; Underwood & Guo, 2018). The recent discovery of contourite drifts immediately seaward of the trench depended on acquisition of high‐quality, high‐resolution seismic reflection data (Tilley et al ., 2021). If one considers both Nankai and Hikurangi, it now seems apparent that occurrences of contourites and contourite–turbidite hybrids are more widespread in modern subduction zones than what was previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…Mulder et al ., 2006; Huppertz & Piper, 2010; Brackenridge et al ., 2013; Gruetzner et al ., 2016; Sansom, 2018; Thieblemont et al ., 2019; Fuhrmann et al ., 2020; Mencaroni et al ., 2021; Miramontes et al ., 2021). That global bias has led to a perception that contourites are unusual or nonexistent in subduction zones, but recent studies of the Nankai system suggest that the perception is probably flawed (Tilley et al ., 2021). Refinements of actualistic facies models for deep‐sea trenches are necessary to advance the broader goals of recognizing facies equivalents and predicting the stratigraphic architecture of ancient (deep‐time) systems.…”
Section: Introductionmentioning
confidence: 99%
“…Very low frequency earthquakes (VLFE) and tremors, which are types of seismic slow earthquakes, have been detected in the shallow megathrust of the Nankai Trough (<30 km) and show a clustered distribution (Figure 1) (Nakano et al., 2018; Ogiso & Tamaribuchi, 2022; Takemura, Matsuzawa, et al., 2019; Takemura, Noda, et al., 2019; Takemura, Baba, et al., 2022; Takemura, Obara, et al., 2022; Tamaribuchi et al., 2022). Previous studies have suggested possible factors affecting the spatial distribution of VLFEs and tremors such as the presence of a subducted seamount (Baba et al., 2023; Sun et al., 2020; Takemura, Matsuzawa, et al., 2019), pore fluid pressure (Hirose et al., 2021; Kitajima & Saffer, 2012; Kodaira et al., 2004), sediment thickness and lithology (Ike et al., 2008; Park and Jamali‐Hondori, 2023; Tilley et al., 2021) and slip‐deficit rate (Yokota et al., 2016).…”
Section: Introductionmentioning
confidence: 99%